GOOD CORPORATE GOVERNANCE, INVESTMENT OPPORTUNITY SET, AND FINANCIAL PERFORMANCE AS A DETERMINANT OF EARNING QUALITY - Ratna Sari Dewi, Cok Istri; Ratih Permata Dewi, I Gusti Ayu (KRISNA: Kumpulan Riset Akuntansi, 2025)
Financial reports contain beneficial information for their users, especially information about profits. Profit information that does not represent the honest truth about the company's economic health, then the quality of its earnings needs to be questioned. Users of financial reports want quality profits. Manipulation of profit quality can lead stakeholders to make wrong decisions in making business decisions about the company. This study aims to determine the effect of Good Corporate Governance, Investment Opportunity Set, and Profitability on profit quality. The population in this study was 45 banking sector companies listed on the Indonesia Stock Exchange in 2020-2022. The sample determination was carried out using the purposive sampling method, namely the selection of samples with several specific criteria, so that a sample of 20 banking sector companies was obtained. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that the good corporate governance variable, proxied by managerial ownership, has a positive effect on profit quality, and then financial performance, proxied by ROA, has a positive effect on profit quality. While the investment opportunity set variable does not affect profit quality. Keywords: managerial ownership, institutional ownership, independent board of commissioners, audit committee, investment opportunity, financial performance